Exploring the interplay between enjoyment, anxiety, ideal self, and willingness to communicate in EMI higher education - Xu, Jian; Zhou, Sihan; Chen, Chen; Perrin, Stuart; Gan, Haiyun (International journal of applied linguistics, 2025)
Learning academic disciplinary knowledge through English as a medium of instruction (EMI) in higher education can be emotionally taxing. However, compared to the bulk of studies investigating the role of emotions in language learning, research that explores students’ emotional experiences in EMI contexts remains scarce. Drawing on a sample of 746 undergraduate students at an EMI university in China, the present study disentangles how two heavily researched emotions (i.e., enjoyment and anxiety) affect students’ learning motivation and willingness to communicate (WTC) inside and outside of EMI classrooms. Students’ motivation is conceptualized through the notion of ideal self to represent their aspired future self‐image as competent language users (ideal L2 self) and subject experts in the field (ideal disciplinary self). Results from structural equation modeling analyses highlighted enjoyment as a strong positive predictor for both ideal selves and WTC. In contrast, anxiety failed to predict neither ideal L2 self nor ideal disciplinary self but had a negative effect on WTC. The two types of ideal selves were found to differ in their respective impact on students’ WTC inside of EMI classrooms yet neither predicted WTC outside of classrooms. Pedagogical implications for EMI teaching and learning are provided. 摘要 在以英语作为教学媒介语言(EMI)的高等教育中, 学习学科知识可能会对英语为非母语的学生带来情绪负担。然而, 目前大多数文献侧重研究情绪在语言学习中的作用, 探索学生在英语媒介语教学情境中情绪体验的研究尚属阙如。本研究选取以英语为媒介语教学的一所中国大学中的746名本科生作为被试, 探究愉悦(enjoyment)和焦虑(anxiety)情绪如何影响学生的学习动机和课堂内外的交际意愿(willingness to communicate)。学生的学习动机通过‘理想自我’(ideal self) 这一理论进行构建, 代表其对成为熟练的外语使用者和优秀的学科专家的未来自我形象构建。基于结构方程模型分析, 研究发现愉悦情绪是理想自我和交际意愿的强正向预测因子。相对而言, 焦虑情绪未能预测理想外语自我或理想学科自我, 并对交际意愿产生负面影响。在英语媒介语教学情境下, 这两种理想自我对学生课堂内交际意愿的影响有所差异, 但均未显著预测课堂外的交际意愿。本研究结果提供了关于英语媒介语教学与学习的启示。